Pendampingan Ibu Hamil dan Suami Dalam Pengenalan Tanda-Tanda Kecemasan Serta Persiapan Perawatan Bayi Baru Lahir Untuk Optimalisasi 1000 Hari Pertama Kehidupan (HPK): Assisting Expectant Couples in Identifying Signs of Anxiety and Preparing for Newborn Care to Optimize the First 1,000 Days of Life - Yuninda Loviana Ersianti; Lidia Aditama Putri; Winda Nur Musfiroh Agustin (Batik-MU : Jurnal Pengabdian Masyarakat, 2026)
The first 1,000 days of life is a critical period that determines the quality of child health, growth, and development; therefore, maternal readiness to care for a newborn should be prepared during pregnancy. Anxiety during pregnancy and limited family support may reduce maternal preparedness for newborn care. This community service program aimed to improve the knowledge of pregnant women and their husbands regarding signs of anxiety and preparation for newborn care to optimize the first 1,000 days of life. The program employed an educational and participatory mentoring approach involving 26 pregnant women in the second and third trimesters and their husbands in Belimbing Sari Village, Sooko District, Mojokerto, from March to April 2026. Activities included pretest assessment, health education sessions, interactive discussions, direct assistance, and post-test evaluation. The results showed that the mean knowledge score increased from 34.6 in the pretest to 90.38 in the post-test. The proportion of respondents with good knowledge also increased from 15.4% to 88.5%. Wilcoxon signed-rank test demonstrated a statistically significant difference before and after the intervention (p=0.000; p<0.05). This program was effective in improving maternal knowledge and readiness for newborn care. Similar educational programs should be implemented continuously with family involvement to support maternal and infant health outcomes.